PHARMACOPHORE-BASED VIRTUAL SCREENING FOR IDENTIFYING POTENTIAL COMPOUNDS AS INHIBITOR OF UROKINASE PLASMINOGEN ACTIVATOR (uPA) - Arfan
The plasminogen activator (PA) system is an extracellular proteolytic enzyme system associated with various physiological and pathophysiological processes. A lot of evidence supports that among the various components of the PA system, urokinase-type plasminogen activator (uPA), its receptor (uPAR), and plasminogen activator inhibitor-1 and -2 (PAI-1 and PAI-2) play a major role in tumor progression and metastasis. Overexpression of uPA and uPAR on the cell surface of tumor cells, resulting in the excessive degradation of ECM, which increases the mobility of cancer cells and facilitates cancer invasion. In the present study, a pharmacophore-based virtual screening method, molecular docking simulation and molecular dynamic simulation were conducted to identify ligands as inhibitors of uPA. The best three pharmacophore models have pharmacophore features, namely M50 model, were built with Aro - Acc&ML –ML - Don&ML&(Acc|Cat); M52 model were built with Aro - Don- ML- Don&ML&(Acc|Cat); and M53 model were built with Aro –Don - Acc&ML - Don&ML&(Acc|Cat) feature using native ligand of uPA (UI3) and mesupron, which was then used to screen the ZINC database using Pharmit. The retrieved virtual hits were subjected to molecular docking simulation analysis using MOE and Autodock Vina. The best six hits of M50, three hits of M52 and one hits of M53 pharmacophore models were subjected to molecular dynamics (MD) simulation, it was observed that each complex was stable during 50 ns MD simulation as indicated by root mean square deviation (RMSD) and root mean square fluctuation (RMSF) values. The result identified one best hit (M52) ZINC000104279905) having better binding potentials than that of mesupron and one equivalent hits (M53) ZINC000095100179) with mesupron as predicted by molecular mechanics Poisson-Boltzmann Surface Area (MM-PBSA) method which can be studied further in the development of new uPA inhibitors.